AMERICAN SELFISHNESS AS REFLECTED IN IRA LEVIN’S “A KISS BEFORE DYING” - Imaniar Imaniar; Ayu Melati Ningsih; Diana Sopha (PHILOLOGY Journal of English Language and Literature, 2021)
This research is entitled "American Selfishness as reflected in Ira Levin’s A Kiss Before Dying”. The purpose of this study is to find out cause of selfishness that reflected American Selfishness that was found in the novel “A Kiss Before Dying” by Ira Levin. The method that has been used in this research is qualitative because this method can provide accurate data. The Data obtained from the novel A Kiss Before Dying consists of 3 Parts and fifteen chapters in each part. Data is also taken from the books and journals concerned with this research. The results showed that there are 2 causes Corliss reflected American selfishness they are stubbornness and rebels, and there are 2 impacts of that selfishness itself they are greedy anddeception.